The effect of load deception on kinetic variables during the second pull from blocks of the power clean - Duggan, J. D.; Moody, J. (ARC Journal of Research in Sports Medicine, 2020)
Strength & conditioning practitioners often seek novel and applied methods to enhance athletic performance. The purpose of this current research was to examine whether `not knowing the load `during a mid-thigh pull (MTP) performance led to enhanced performance characteristics across a randomised selection of loads (75%-95% 1RM). Fifteen male collegiate athletes (age 21.8 ± 2.3, height 171.8 ± 7.5 cm, mass 89.3kg ± 9.8kg, MTP 1RM 135.5kg ± 18kg) were selected for the pre 1RM MTP and the 5 post randomised unknown lifts between 75%-95% of individual 1RM. The research demonstrated that unknown loads at 75% 1RM lead to significant changes in average power (AP) (known1062±251 W, unknown1213 ± 289W; p = 0.05; effect size (ES) = 0.56 small). Unknown loads at 75% 1RM lead to significant changes in average velocity (AV) (known: 0.49±0.1, unknown: 0.66 ± 0.10m/s; p = 0.00; ES = 1.66 large). There was also a significant change in peak velocity (PV) at 75% 1RM (known: 0.74±0.16, unknown: 0.95 ± 0.26m/s; p = 0.05; ES = 0.99 moderate). Unknown loads at 80% 1RM lead to significant changes in AV (known: 0.47±0.10 unknown: 0.60 ± 0.10m/s; p = 0.01; ES = 1.36 large). There was no significant difference in AP, AV, peak power (PP) and PV variables across 85, 90, 95% 1RM (p = 0.05; ES = trivial to small). It appears that these findings especially at unknown loads between 75% and 80% 1RM could be beneficial in enhancing velocity-based performance variables. Therefore, the applications of unknown loads are of meaningful practical use to enhance performance variables during weightlifting pulling derivatives. Therefore, weightlifting pulling derivatives are potentially a useful training modality to improve desirable ballistic actions in particular triple extension.